Carbon Emission Disclosure, Carbon Performance, and Firm Value: Exploring Intellectual Capital’s Role - Luthfi Darmawan; Amrie Firmansyah (Jurnal Dinamika Akuntansi, 2025)
Purposes: This study investigates the impact of carbon emission disclosure and carbon performance on firm value, with intellectual capital as a moderating variable. The research addresses the increasing importance of sustainability disclosures and their effect on corporate valuation, particularly in the mining sector, which significantly contributes to global carbon emissions. Methods: This research employs a quantitative method by examining data from 63 mining companies listed on the Indonesia Stock Exchange (IDX) for 2020–2023. Through purposive sampling, 34 companies were selected, resulting in 94 observations. The data were analyzed using unbalanced panel data regression with the help of STATA software. Findings: The results show that carbon emission disclosure negatively impacts firm value, while carbon performance positively influences firm value. However, intellectual capital does not moderate the relationship between carbon emission disclosure, carbon performance, and firm value. Novelty: This research highlights the limited role of intellectual capital in enhancing the effects of sustainability practices on firm value, providing new insights into its integration within corporate strategies. It emphasizes the need for companies and policymakers to optimize intellectual capital utilization in sustainability practices to improve corporate value. Future studies could explore other industries or incorporate additional moderating variables for a more comprehensive analysis.